2021
DOI: 10.1111/eci.13650
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 phospholipids and obesity‐associated NAFLD: Potential mechanisms and therapeutic perspectives

Abstract: Prevalence of non-alcoholic fatty liver disease (NAFLD) increases in line with obesity and type 2 diabetes, and there is no approved drug therapy. Polyunsaturated fatty acids of n-3 series (omega-3) are known for their hypolipidaemic and antiinflammatory effects. Existing clinical trials suggest varying effectiveness of triacylglycerol-or ethyl ester-bound omega-3 in the treatment of NAFLD, without affecting advanced stages such as non-alcoholic steatohepatitis. Preclinical studies suggest that the lipid class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 101 publications
(219 reference statements)
0
14
0
Order By: Relevance
“…In regard to the relationship between total PUFAs and risk of NAFLD, a systematic review and meta-analysis of 13 studies, consisting of 668 patients with NAFLD, found that total PUFAs or fish oil supplementation may affect serum ALT levels and improve liver function (28). Similar associations could also be observed in other studies of dietary or supplementation with n-3 fatty acids (29)(30)(31)(32). However, contradictory results could also be found.…”
Section: Discussionmentioning
confidence: 73%
“…In regard to the relationship between total PUFAs and risk of NAFLD, a systematic review and meta-analysis of 13 studies, consisting of 668 patients with NAFLD, found that total PUFAs or fish oil supplementation may affect serum ALT levels and improve liver function (28). Similar associations could also be observed in other studies of dietary or supplementation with n-3 fatty acids (29)(30)(31)(32). However, contradictory results could also be found.…”
Section: Discussionmentioning
confidence: 73%
“…The peptides isolated from sea cucumber Stichopus japonicas can increase the content of unsaturated lipids in mouse and rat hippocampus (Lu et al, 2022a). As unsaturated lipids can modulate lipid metabolism (Djuricic and Calder, 2021;Mitrovic et al, 2022), the above results suggest that peptides alleviate hyperlipidemia by regulating the metabolism of unsaturated lipids. The potential mechanisms of action of peptides and proteins of sea cucumbers are summarized in Figure 9.…”
Section: Protein and Peptidementioning
confidence: 88%
“…Different solvents have distinct ability for extraction of FAs, and water is found to Frontiers in Pharmacology frontiersin.org have a higher efficiency for extraction of docosahexaenoic acid (C22:6, Figure 1) compared to phosphate buffer saline, methanol, or ethanol (Fredalina et al, 1999). Accumulating evidence have demonstrated the health-beneficial effects of polyunsaturated FAs for treatment of lipid disorders (Djuricic and Calder, 2021;Mitrovic et al, 2022). Therefore, FAs, especially the n-3 polyunsaturated FAs that are enriched in sea cucumbers have potential application in pharmaceutical industries for intervention of dyslipidemias.…”
Section: Fa and Phospholipidmentioning
confidence: 99%
“…Phospholipids are increasingly being studied, as their oxidation may be associated with obesity, inflammation, and NASH. It has been reported that carbon chain (C)32, C34, and C36 are inversely related to the severity of NAFLD [ 40 ], that n -3 PUFA has anti-inflammatory effects in the liver [ 41 ], and that neutralizing oxidized phospholipids are effective treatment for NASH in studies in mice [ 42 ]. It has been reported that the increase in FFAs after LSG may be due to the mobilization of FFAs from adipose and hepatic tissues due to decreased dietary intake and decreased substrate availability for de novo lipid synthesis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%